Incidence of and risk factors for mortality in children with mushroom poisoning - Jie Cheng; Ya Liu; Shaojun Li; Kaibin Pu; Junming Huo; Liping Tan (International Journal of Emergency Medicine)
Abstract Objective We aimed to evaluate the incidence of and risk factors for mortality in children with mushroom poisoning. Methods Sixty-seven children with mushroom poisoning who were hospitalized at the Children’s Hospital of Chongqing Medical University were retrospectively enrolled. The clinical characteristics of the children in the surviving and non-surviving groups were compared. Variables with a P value < 0.1 in the univariate logistic regression analysis were included in the multivariate logistic regression analysis. A receiver operating characteristic (ROC) curve was generated to determine the optimal cutoff point. Results The mortality rate of children with mushroom poisoning was 23.88% (16/67), and the incidence of death during hospitalization was 35.02 per 1,000 person-days. The median pediatric sequential organ failure assessment (pSOFA) score was 1.00 (interquartile range [IQR] 0.00–3.00). Logistic regression analysis revealed that the pSOFA score was independently associated with mortality (odds ratio [OR] 4.92, 95% confidence interval [CI] 1.59–62.21; P = 0.040). The optimal cutoff point of the pSOFA score for predicting mortality was 2.00, with an area under the curve (AUC) of 0.84 (95% CI 0.71–0.88, P < 0.001*). Conclusions In this study, the incidence of death among children with mushroom poisoning was retrospectively evaluated. The pSOFA score may serve as a good prognostic indicator in children with mushroom poisoning, and children with a pSOFA score ≥ 2 have a significantly increased risk of mortality.